Implementasi Kebijakan Penataan Ruang Terbuka Hijau Publik Di Kabupaten Sidoarjo - Yurrike Chintya Dewi; Isna Fitria Agustina (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2018)
This research was conducted aiming to describe and analyze the implementation of the public green open space structuring policy in Sidoarjo Regency and to describe and analyze the constraints in the public green open space structuring policy in Sidoarjo Regency. The method used in this study is a descriptive qualitative method with the technique of determining the informants using purposive sampling technique. Data collection techniques through interviews, observation, and documentation as well as data analysis techniques through data reduction, data presentation, and conclusion drawing. The results of this study indicate that of the four dimensions of policy implementation according to Edward III which includes communication, resources, disposition, and bureaucratic structure. The first dimension result is that communication has not gone well because there is no information delivery to the public in the form of socialization related to green open space. Resources in the implementation of public green open space structuring policies are inadequate. Disposition in the implementation of the public green open space structuring policy is appropriate and the gardening section as the implementer of the green space program. The bureaucratic structure has not gone well due to the absence of SOP (Standard Operating Procedure) as a guideline for program implementation and found several obstacles that hamper the implementation process, namely budget constraints, lack of field supervisors, and lack of community participation due to lack of socialization.